2020
DOI: 10.3390/rel11020064
|View full text |Cite
|
Sign up to set email alerts
|

Centrality of Religiosity Scale in Polish Research: A Curvilinear Mechanism that Explains the Categories of Centrality of Religiosity

Abstract: The centrality of religiosity scale (CRS) is a measure of the importance of religious constructs in personality. The Polish CRS has been applied in more than 40 published studies on the psychology of religion, with over 18,000 total participants. However, no comprehensive overview on the Polish CRS is available. This paper shows how using the CRS sheds light on different patterns in which religion integrates with other psychological variables. It consists of three parts: first, we introduce the Polish adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
1
27
1
Order By: Relevance
“…Thus, the religious meaning system can facilitate individuals to explain forgiveness in terms of significance and purpose and establish its connections with meaning in life. These results further support Huber's (2008) claim that the religiosity status may affect the way in which various psychological variables operate and how they affect people's psychological functioning (Zarzycka et al 2020). These results are in line with previous studies which have consistently confirmed religiosity as a predictor of engagement in forgiveness-oriented activities (Laufer et al 2009).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, the religious meaning system can facilitate individuals to explain forgiveness in terms of significance and purpose and establish its connections with meaning in life. These results further support Huber's (2008) claim that the religiosity status may affect the way in which various psychological variables operate and how they affect people's psychological functioning (Zarzycka et al 2020). These results are in line with previous studies which have consistently confirmed religiosity as a predictor of engagement in forgiveness-oriented activities (Laufer et al 2009).…”
Section: Discussionsupporting
confidence: 90%
“…Next, the religious meaning system can also moderate the relationship between forgiveness and meaning in life. Theoretical assumptions and empirical findings (Huber and Huber 2012) provided support for the claim that the religiosity status can affect the way in which various religious contents relate to people's psychological functioning (Zarzycka et al 2020). For example, based on the personal construct theory, Huber (2007) claimed that when the religious construct is salient in the personal construct system, it has a much stronger relevance for general psychological dispositions than when it is placed in a subordinate or a marginal position.…”
Section: Introductionmentioning
confidence: 95%
“…The CRS Scale by Huber in its Polish adaptation by (Zarzycka 2007(Zarzycka , 2011Zarzycka et al 2020) is a measure of the centrality of religiosity, i.e., the position of a system of religious constructs in human personality. It consists of five sub-scales: (1) Intellect, i.e., the frequency and importance of cognitive confrontation with religious content, without taking into account the aspect of their personal acceptance; (2) Ideology-the degree of subjectively assessed probability of the existence of transcendent reality and the intensity of openness to various forms of transcendence; (3) Private Practice-the frequency of contact with transcendent reality and the subjective meaning of that contact for an individual (personal prayer); (4) Religious Experience-the frequency with which transcendence becomes part of human experience and the extent to which the transcendent world of religious meanings is individually confirmed by the sense of communication and action; (5) Public Practice-the frequency and subjective meaning of human participation in religious services.…”
Section: Centrality Of Religiosity Scale (Crs)mentioning
confidence: 99%
“…The objective frequencies were recoded into five levels of subjective frequencies. The Polish version of the CRS showed appropriate psychometric properties (Zarzycka 2007(Zarzycka , 2011). Cronbach's alpha was satisfactory in this sample (Table 2).…”
Section: Centrality Of Religionmentioning
confidence: 99%